The Holobiont Blindspot: Relating Host-Microbiome Interactions to Cognitive Biases and the Concept of the “Umwelt” - Robinson, Jake M.; Cameron, Ross (Frontiers in Psychology, 2020)
Cognitive biases can lead to misinterpretations of human and non-human biology and behaviour. The concept of the Umwelt describes phylogenetic contrasts in the sensory realms of different species and has important implications for evolutionary studies of cognition (including biases) and social behaviour. It has recently been suggested that the microbiome (the diverse network of microorganisms in a given environment, including those within a host organism such as humans) has an influential role in host behaviour and health. In this paper, we discuss the host’s microbiome in relation to cognitive biases and the concept of the Umwelt. Failing to consider the role of host–microbiome (collectively termed a ‘holobiont’) interactions in a given behaviour, may underpin a potentially important cognitive bias––which we refer to as the Holobiont Blindspot. We also suggest that microbially-mediated behavioural responses could augment our understanding of the Umwelt. For example, the potential role of the microbiome in perception and action could be an important component of the system that gives rise to the Umwelt. We also discuss whether microbial symbionts could be considered in System 1 thinking––that is, decisions driven by perception, intuition and associative memory. Recognising Holobiont Blindspots and considering the microbiome as a key factor in the Umwelt and System 1 thinking has the potential to advance studies of cognition. Furthermore, investigating Holobiont Blindspots could have important implications for our understanding of social behaviours and mental health. Indeed, the way we think about how we think may need to be revisited.